1993
DOI: 10.1002/mrd.1080340302
|View full text |Cite
|
Sign up to set email alerts
|

Acrogranin, an acrosomal cysteine‐rich glycoprotein, is the precursor of the growth‐modulating peptides, granulins, and epithelins, and is expressed in somatic as well as male germ cells

Abstract: Spermatogenesis is a unique system of differentiation involving cellular remodeling and the biogenesis of sperm-specific organelles. To study the biogenesis of one such organelle, the acrosome, we have been examining the gene expression, biosynthesis, and targeting of specific acrosomal proteins during mammalian spermatogenesis. An acrosomal marker that we recently purified and began characterizing is acrogranin, a 67,000-molecular-weight glycoprotein originally isolated from guinea pig testes. This glycoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 25 publications
5
103
0
2
Order By: Relevance
“…Granulins were first purified from the extracts of human inflammatory cell exudates, and from rat bone marrow (1). To date, seven granulin peptides (A to G) have been characterized (9,10,26,27), and it has been shown that they are generated following proteolytic cleavage of progranulin (7). The two main differences between goldfish granulin and mammalian progranulin were: (a) the goldfish granulin gene encoded for a much smaller protein (159 amino acids); and (b) unlike mammalian progranulin, which has been shown to be expressed ubiquitously in different tissues, the goldfish granulin expression was limited to hematopoietic tissues (kidney and spleen) and blood mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Granulins were first purified from the extracts of human inflammatory cell exudates, and from rat bone marrow (1). To date, seven granulin peptides (A to G) have been characterized (9,10,26,27), and it has been shown that they are generated following proteolytic cleavage of progranulin (7). The two main differences between goldfish granulin and mammalian progranulin were: (a) the goldfish granulin gene encoded for a much smaller protein (159 amino acids); and (b) unlike mammalian progranulin, which has been shown to be expressed ubiquitously in different tissues, the goldfish granulin expression was limited to hematopoietic tissues (kidney and spleen) and blood mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%
“…The larger precursor is known by several names, including granulin/epithelin precursor (8), proepithelin (9), acrogranin (10), PC cell-derived growth factor (PCDGF) (11), and progranulin. Granulins have a unique 12-cysteine motif that is arranged in four ␤-hairpins, stacked one upon another in a helical formation and connected via a central rod of disulfide bonds (12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mammalian GRN gene encodes a multifunctional secreted glycoprotein with tandem repeats of cysteine-rich GRN modules (1,(36)(37)(38)(39) (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…1A). It is known synonymously as PGRN, (8) granulin-epithelin precursor (GEP), (40) proepithelin, (38) PC cell-derived growth factor (PCDGF), (10) acrogranin, (39) and epithelial transforming growth factor (TGFe). (41) This rather dense nomenclature for a single gene is revealing since it captures many of the essential features of the biology of PGRN.…”
Section: Introductionmentioning
confidence: 99%